BRM920: Quantitative research methods analysis / Arshad Ayub Graduate Business School - UiTM, Arshad Ayub Graduate Business School (2022)
This is a hands-on approach course where statistical tools (statistical software’s – SPSS. Smart PLS, Rs) for statistical analysis at elementary and advanced level are introduced and used.